Quality of Liquid Organic Fertilizer Peanut Shells and Tofu Dregs With Banana Stems as Bioactivator - Kahfi, Muhammad Rizal; Asngad, Aminah (Universitas Muhammadiyah Surakarta, 2023)
Liquid organic fertilizer is nutrition given to plants to improve the supply of nutrients so that plants can grow well. The utilization of peanut shells and tofu dregs has the potential as liquid organic fertilizer and banana stems as a bioactivation. This study aimed to determine the quality of liquid organic fertilizer, a combination of peanut shells and tofu dregs, adding moles of banana stems as a bioactivator. This study used experimental methods and a Completely Randomized Design (CRD) consisting of 2 factors and 4 combinations with 3 repetitions. Factor 1 combines peanut shells and tofu waste K1 = 100 ml: 200 ml and K2 = 120 ml: 180 ml. Factor 2 is the local microorganism concentration, namely M1 = 100ml and M2 = 200ml. Data were analyzed using descriptive qualitative and quantitative. The results showed that the fertilizer had a yellowish brown and light brown color, a slightly pungent fermented to not overpowering, and a pH of 4. The highest N was in K1M1 combination of 0,57%, the highest P in K1M1 and K2M1 was 0,05%, and the highest K in K1M1 of 0,08%. It can be concluded that liquid organic fertilizer has good quality complies with SNI 19-7030-2004.